Exploring Group Dynamics in Activity-Based Group Work with Young People Experiencing Homelessness. Issue 4 (1st October 2016) - Kelly, Brian L.; Hunter, Margaret Joan
ABSTRACT: This article explores the development of group dynamics in an activity-based group comprising four young people experiencing homelessness and one group facilitator. Over the course of 12 sessions, the group produced a coconstructed audio documentary. Nine group sessions were recorded, transcribed, coded, and analyzed for patterns of group dynamics, including communication and interaction patterns, cohesion, social integration and influence, and culture. Findings suggest that the task-oriented nature of coproducing the audio documentary facilitated the development of interpersonal dynamics, provided young people with opportunities for personal growth, and provided them with opportunities to engage their strengths as well.